The Rim Cutter does not show an advantage over modern cementing techniques: a five-year radiological and clinical follow-up of the Rim Cutter used with flanged acetabular components. (November 2017) - vanWinterswijk, P. J. T. S.; Whitehouse, S. L.; Timperley, A. J.; Hubble, M. J. W.; Howell, J. R.; Wilson, M. J.
Abstract : Aims: We report the incidence of radiolucent lines (RLLs) using two flanged acetabular components at total hip arthroplasty (THA) and the effect of the Rim Cutter. Patients and Methods: We performed a retrospective review of 300 hips in 292 patients who underwent primary cemented THA. A contemporary flanged acetabular component was used with (group 1) and without (group 2) the use of the Rim Cutter and the Rimfit acetabular component was used with the Rim Cutter (group 3). RLLs and clinical outcomes were evaluated immediately post-operatively and at five years post-operatively. Results: There was no significant difference in the incidence of RLLs on the immediate post-operative radiographs (p = 0.241) or at five years post-operatively (p = 0.463). RLLs were seen on the immediate post-operative radiograph in 2% of hips in group 1, in 5% in group 2 and in 7% in group 3. Five years post-operatively, there were RLLs in 42% of hips in group 1, 41% in group 2 and in 49% in group 3. In the vast majority of hips, in each group, the RLL was present in DeLee and Charnley zone 1 only (86%, 83%, 67% respectively). Oxford and Harris Hip scores improved significantly in all groups. There was no significant difference in these scores or in the change in scores between the groups, with follow-up. Conclusion: Despite the Rim Cutter showing promising results in early laboratory and clinical studies, this analysis of the radiological and clinical outcome five years post-operatively does not show any advantage over and above modern cementing techniques in combination with a well performing cemented acetabular component. For this reason, we no longer use the Rim Cutter in routine primary THA. Cite this article: Bone Joint J 2017;99-B:1450–7.